2018
DOI: 10.4103/ijmr.ijmr_1807_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypovitaminosis D in India & way forward

Abstract: Deficiency of vitamin D or hypovitaminosis D is widespread irrespective of age, gender, race and geography and has emerged as an important area of research. Vitamin D deficiency may lead to osteoporosis (osteomalacia in adults and rickets in children) along with calcium deficiency. Its deficiency is linked with low bone mass, weakness of muscles and increased risk of fracture. However, further research is needed to link deficiency of vitamin D with extra-skeletal consequences such as cancer, cardiovascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 37 publications
0
32
0
2
Order By: Relevance
“…Though India is a subtropical country with adequate sunlight, vitamin D deficiency is prevalent. 18 However, there remain two concerns regarding vitamin D supplementation and disease outcomes. First, the appropriate levels of 25 (OH)D for its immunomodulatory effects are not known.…”
Section: Resultsmentioning
confidence: 99%
“…Though India is a subtropical country with adequate sunlight, vitamin D deficiency is prevalent. 18 However, there remain two concerns regarding vitamin D supplementation and disease outcomes. First, the appropriate levels of 25 (OH)D for its immunomodulatory effects are not known.…”
Section: Resultsmentioning
confidence: 99%
“…In Japan, Miyamoto et al reported that among women aged 39 to 49 years, 31.6% had 25-hydroxyvitamin D deficiency (<20 ng/mL), 47.4% had suboptimal level (20-30 ng/mL), and only 21% had normal level (>30 ng/mL) [ 4 ]. Causes of vitamin D deficiency include length and timing of sun exposure, the amount of skin exposed to sunlight, application of sunscreen, insufficient intake of vitamin D, and abnormalities associated with chronic kidney disease [ 5 ]. In this case, the proband did not have excessive sunlight avoidance or an unbalanced diet, and her renal function was normal.…”
Section: Discussionmentioning
confidence: 99%
“…Во всем мире существует проблема низкой информированности родителей о роли витамина D в организме, источниках его поступления, последствиях дефицита и организации профилактического приема препаратов витамина D. При этом лишь каждый 4-й ребенок в возрасте до 2 лет получает профилактическую дозу холекальциферола [17]. Большинство взрослых также не осведомлены и не принимают витамин D [18][19][20][21].…”
Section: таблица 5 уровень 25(он)d3 в плазме крови у детей в зависимости от сезона года и длительности инсоляции Table 5 Level 25(oh)d3 Dunclassified